FAKTOR YANG MEMPENGARUHI PURCHASE BEHAVIOR DALAM BERBELANJA ONLINE DI APLIKASI TOKOPEDIA - Haryanti, Denny Septa; Sa roni, Putri Istiadah Oktafia (Solusi, 2022)
The purpose of this research is to investigate purchasing behavior of online shopping in the spectrum of brand consciousness, brand awareness, and brand nationality. The study uses a well structured questionnaire developed and distributed to 180 respondent, but only 170 respondent to conform the criteria. Using purposive sampling method, and data were analyzed by applying IBM SPSS 25.0 and Structural Equation Modeling (SEM) program WarpPLS 7.0. The results show that brand consciousness influence to purchase behavior, brand awareness not affect to purchase behavior, and brand nationality influence to purchase behavior.